Establishing the feasibility of assessing the mental health of children displaced by the Syrian conflict. (19th June 2015) - Cartwright, K.; El-Khani, A.; Subryan, A.; Calam, R.
Abstract : Background: In the humanitarian crisis context of conflict zones, collecting data is essential for identifying and addressing the mental health needs of refugee children to avoid mass suffering. This study tested the feasibility of recruiting refugees caring for children and using established and brief parent-report questionnaires in a challenging context to collect mental health data on refugee children displaced by Syria's conflict. Methods: Caregivers of 4–10-year olds attending primary schools run by non-governmental organisation (NGO) Generation Freedom in and near refugee camps on the Syrian–Turkish border were invited to complete the Pediatric Emotional Distress Scale (PEDS) and Strengths and Difficulties Questionnaire (SDQ). Results: It was possible to reach 144 adult refugees caring for children with research participation information and use informed consent procedures. A total of 106 caregivers completed the questionnaires yielding a good return rate (74%). Eighty-two (77.4%) caregivers had complete data on the PEDS and 61 (57.5%) on the SDQ. Almost half (49%) of the children met the clinical cut-off for being anxious/withdrawn and 62% for being fearful rated using the PEDS and 45% for SDQ rated emotional symptoms. More than a third had clinical levels of behavioural problems on both scales. Conclusions: It proved feasible to collect child mental health data in challenging conditions in the context of the Syrian crisis with support from a local NGO providing humanitarian assistance. The PEDS performed better than the SDQ in this context. High levels of emotional distress and behavioural problems in children reiterate the urgent need for evidence-based psychosocial support.